Adopsi Teknologi Pengelolaan Tanaman Terpadu Padi Sawah Oleh Petani (Studi Kasus Petani Desa Tumiyang Kecamatan Pekuncen Kabupaten Banyumas) - Mulyani, Sri; Hartati, Puji; Puspitojati, Endah (Agrimas : Jurnal Pengabdian Masyarakat Bidang Pertanian, 2023)
This study aims to determine the level of adoption of lowland rice PTT technology in Tumiyang Village, Pekuncen District, Banyumas Regency. The study was carried out from January 2023 to June 2023 in Tumiyang Village, Pekuncen District, Banyumas Regency. This study is a research using descriptive qualitative analysis method. Data collection techniques by means of observation (observation), interviews, and literature study in which data analysis using Test Item Testing and Descriptive Analysis, and Analysis and carried out with a sample of 62 respondents. The result of the research is that all questions are declared significant with a significance level above 0.250. The results of the research are used as the basis for the design of empowerment and implementation of counseling by increasing the use of natural enemies as an IPM (Integrated Pest Control) effort, as an effort to increase farmers' adoption of PTT rice paddy technology. the methods used are lectures, discussions, and practice. The results of empowerment are increasing the knowledge of farmers by 39.58%, the attitude of farmers by 41.49%, and the skills of farmers by 45.05%